Relationship between school principal's facilitator style and ICT utilization among secondary school teachers / Mazzuana Mohammad Mathias - Mohammad Mathias, Mazzuana (2013)
The purpose of the study is to examine the relationship between school principal's facilitating style and ICT utilization among secondary school teachers. This study involves 11 schools in Kuching Division with a total of 414 randomly selected teachers as sample. The teachers evaluate their principal's facilitating style and also to determine the ICT utilization among secondary school teachers. The types of statistical analysis been used was descriptive statistics which is to indicate the composition of the respondents and distribution of demographic. Independent T-test and One-way ANOVA were used to analyze the differences of means on principal's facilitating style and selected demographic characteristics of secondary school teachers. Furthermore. Pearson correlation coefficient was used to examine the relationship between the school principal style and ICT utilization among secondary school teachers. Results showed that the Initiator Style was perceived as dominant style with the highest mean score of 3.88, followed by Managerial Style with mean score of 3.78 and Responder Style recorded the lowest mean score of 3.60. There is no significant difference of principal's facilitating style and teacher's demographic towards all the three principal's facilitating style except for teacher's gender towards Managerial Style. Based on the Pearson Correlation test, the significant relationship exists between ICT utilization among the secondary school teachers and Initiator Style, Managerial Style and Responder Style with r = .320, pO.Ol; r = .336 pO.Ol; r= .319 pO.Ol respectively. The highest correlation value for the findings on the relationship between principal's facilitating style and the ICT utilization is Managerial Style followed by Initiator Style and Responder Style respectively. Thus it is recommended that appropriate facilitating style such as Managerial Style and Initiator Style for principals to enhance their capabilities in engaging ICT utilization among secondary school teachers.